Leveraging Financial Technology Entity into Sustainable Bank Performance through a Competitive Advantage - Steph Subanidja; Fangky Antoneus Sorongan; Mercurius Broto Legowo (Ital Publication, 2022)
The study investigates the existence of a fintech entity that effect sustainable bank performance through competitive advantage and introduces a new fintech entity as an antecedent of competitive advantage and performance. Analysis of the causes of disturbance of the performance uses quantitative and qualitative approaches. The study uses 59 questionnaires returned from all 70 bank financial managers as a National Commercial Bank Association member. Five informants were selected from the Central Bank of Indonesia, the Financial Services Authority, the Indonesian Fintech Association, a bank business player, and the Commercial Bank Association Management. Using Partial Least Square, the results show that the fintech entity can drive sustainable bank performance, directly and indirectly, through competitive advantage. The existence of fintech is a dominant factor for achieving performance. From the informants, the results show that collaboration with a fintech entity is necessary and initially, the banks in running a business based on a perspective of experience. Moreover, Informants predicted that fintech and competitive conditions would significantly influence performance in the present and the future. Then, the implication is that fintech cannot be avoided but must be embraced as bank cooperation partners to sustain the performance. Doi: 10.28991/ESJ-2022-06-01-04 Full Text: PDF